Šabac: A Cinematographic Archaeology? - Kador, Thomas; Lukic, Vesna (Journal of Contemporary Archaeology, 2018)
Drawn from a longstanding collaboration between the authors, this contribution explores the common ground between filmmaking and archaeological investigation and in particular a shared interest in haptic experiences and the material properties of the world. This leads us to propose the use of the camera and the moving image it produces as valuable archaeological research tools. To illustrate this we present both a short film and brief discussion paper focusing on the Serbian town of Šabac as a Holocaust landscape and its link with a group of Jewish refugees known as the “Kladovo transport”. Based on this case study we aim to highlight the transformative potential of artistic interventions in archaeological questions, and indeed vice versa, to construct new modes of knowing.